CONFORMAL CORRESPONDENCE BETWEEN FRIEDMAN TYPE SOLUTIONS IN GENERAL RELATIVITY AND JORDAN–BRANS–DICKE THEORY OF GRAVITY - Piloyan, A. S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2023)
Solutions for the cosmological problem are obtained by using the conformal transformations connecting general relativity and Jordan–Brans–Dicke theory of gravity. The cases of equations of stat P = 13ε and P=0 are considered.